THE MARCH 25, 2020 MW=7.5 PARAMUSHIR EARTHQUAKE AND ITS IMPACT ON RECENT GEODYNAMICS OF THE ADJACENT SECTION OF THE KURIL-KAMCHATKA SUBDUCTION ZONE - A. S. Prytkov; N. F. Vasilenko (Геодинамика и тектонофизика)
An intraplate tsunamigenic earthquake with МW=7.5 occurred on March 25, 2020 southeast of the Paramushir Island (Kuril Islands) beneath the outer slope of the Kuril-Kamchatka Trench. Since 1900, this earthquake has been the largest event for an 800-km long oceanic slope and a 300-km long segment of the Kuril seismofocal zone located near the epicenter. Sub-horizontal compression stresses generated in the earthquake source region were oriented across the seismofocal zone. A type of motion is represented by reverse faulting along the both nodal planes.The compressive stress state in which there occurred the Paramushir earthquake reflects the present-day geodynamics in the subduction zone near the hypocenter. The paper shows that the earthquake occurrence is due to a strong mechanical contact surface between the Pacific and North American lithospheric plates in the subduction zone. The analysis of coseismic displacement of the nearest Global Navigation Satellite System (GNSS) station served as confirmation of the determination of fault plane solution of the earthquake. A seismogenerating motion occurred along the plane oriented to the southwest and dipping towards the trench. For Finite fault source models, there were calculated the increments of the Coulomb stress in the subduction zone. For the main fault plane, the increment of the Coulomb stress in the interpolate contact area propagates to a depth of ~30 km and reaches 1 bar.Coseismic stress increment in the subduction zone at the northern flank of the Kuril island arc, which has a high seismic potential at the present stage of the tectonic cycle, increases the likelihood of the largest interplate earthquake occurrence therein.